2020
DOI: 10.1002/acm2.13040
|View full text |Cite
|
Sign up to set email alerts
|

A simple dosimetric approach to spatially fractionated GRID radiation therapy using the multileaf collimator for treatment of breast cancers in the prone position

Abstract: The purpose of this study was to explore the treatment planning methods of spatially fractionated radiation therapy (SFRT), commonly referred to as GRID therapy, in the treatment of breast cancer patients using multileaf collimator (MLC) in the prone position. A total of 12 patients with either left or right breast cancer were retrospectively chosen. The computed tomography (CT) images taken for the whole breast external beam radiation therapy (WB‐EBRT) were used for GRID therapy planning. Each GRID plan was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In addition, dosimetric and geometric characteristics of the heterogeneous dose distribution, such as dose volume histogram characteristics (D10, D50, D90) and peak-to-peak distance, should be reported according to guidelines further described in the recent GRID physics and dosimetry white paper. 22 Owing to the different SFRT technologies (eg, collimator-based and MLC-based GRID) with different dose distributions, 34 the equivalent uniform dose (EUD) for H&N squamous cell carcinoma (using α/β = 10 Gy) and for normal tissues (generally α/β = 3 Gy) must be determined for any trial regimen. Principles of EUD computation in SFRT, which favor the modified linear quadratic model, and tumor cell sensitivity considerations are described in the recent SFRT physics guideline publications.…”
Section: Consensus Guideline Recommendations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dosimetric and geometric characteristics of the heterogeneous dose distribution, such as dose volume histogram characteristics (D10, D50, D90) and peak-to-peak distance, should be reported according to guidelines further described in the recent GRID physics and dosimetry white paper. 22 Owing to the different SFRT technologies (eg, collimator-based and MLC-based GRID) with different dose distributions, 34 the equivalent uniform dose (EUD) for H&N squamous cell carcinoma (using α/β = 10 Gy) and for normal tissues (generally α/β = 3 Gy) must be determined for any trial regimen. Principles of EUD computation in SFRT, which favor the modified linear quadratic model, and tumor cell sensitivity considerations are described in the recent SFRT physics guideline publications.…”
Section: Consensus Guideline Recommendations and Discussionmentioning
confidence: 99%
“…Because of the different SFRT technologies (e.g. collimator-based and MLC-based GRID) with different dose distributions 34 , the equivalent uniform dose (EUD) for H&N squamous cell carcinoma (employing α/β=10 Gy) and for normal tissues (generally α/β=3 Gy) must be determined for any trial regimen. Principles of EUD computation in SFRT, which favor the modified linear quadratic model, and tumor cell sensitivity considerations are described in the recent SFRT physics guideline publications 22 25 .…”
Section: Radiation Therapymentioning
confidence: 99%
“…Their simulation demonstrated that the 3D conformal MLC-based GRID resulted in enhanced target coverage with reduced skin and organs at risk toxicity. Using a similar approach in a cohort of patients consistently with breast cancer, Murphy et al demonstrated that the dosimetric qualities of MLC-based GRID plans were comparable with block-based GRID with the added advantage of superior conformity for MLC-based plans [ 88 ]. Plan evaluations were conducted in terms of the EUD and TR using DVH curves.…”
Section: Preclinical and Clinical Evidence With Spatially Fractionate...mentioning
confidence: 99%
“…GRID and FLASH therapies have in common a highly heterogeneous dose distribution, very high prescription doses and an overall lack of experience among physicists and clinicians. 16 , 17 …”
Section: Opening Statementsmentioning
confidence: 99%